The Effect of Taste and Service Quality on Customer Satisfaction in Pertamax Mie Ayam Bakso, Kaur Regency - Imam Ade Mahfud; Ahmad Soleh; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2021)
The entrepreneurs must find a way to win the market and get the attention of consumers. They must able to create something new that can attract customer satisfaction such as the taste of the food and the quality of service. Based on the background, this study was intended to determine the effect of taste and service quality on customer satisfaction at Mie Ayam Bakso Pertamax, Kaur Regency. The sample in this study was 124 customers who purchased rib-eye meatballs at Mie Ayam Bakso Pertamax, Kaur Regency. The data in this study was collected by using a questionnaire which then analyzed by using multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 18,779 + 0,278X1 + 0,423 X2 + 3,251 which showed a positive regression direction. There is positive influence between X1 (taste) and X2 (quality of service) on customer satisfaction (Y). It means that if the variables of taste and service quality increase, it will increase customer satisfaction. The magnitude of the coefficient of determination is 0.310. This means that X1 (taste) and X2 (quality of service) affect customer satisfaction (Y) by 31% while the remaining 69% is influenced by other variables which are not examined in this study. The results of the t test at a significance level of 0.05 explained that partially the taste and service quality variables had a significant influence on the customer satisfaction variable for Mie Ayam Bakso Pertamax, Kaur Regency. Finally, The result of the F test at a significance level of 0.05 explains that the variables of taste and service quality have a simultaneous effect on customer satisfaction at Mie Ayam Bakso Pertamax, Kaur Regency.